Fluid Enquiry, Complex Causality, Policy Processes: Making a Difference with Qualitative Longitudinal Research. Issue 4 (19th October 2021) - Neale, Bren
Abstract : In this article, qualitative longitudinal (QL) research is presented as a powerful form of fluid enquiry. The combination of its real-world and real-time features enables this methodology to 'follow reality in all its windings', and, thereby, to produce useful knowledge for policy and professional practice. The main focus is on the power of QL methodology to illuminate complex causal processes by teasing out their multiple, fluid and relational elements. The article goes on to consider new ways to broker the interface between research endeavours and policy processes, based on collaborative modes of knowledge co-production that unfold in real-time. QL enquiry emerges here as more than an added option, a 'niche' approach. It has potential as a valuable 'impact' tool for discerning causality in new ways and reformulating insights into 'what works?', with scope to play a pivotal role in shaping and facilitating change in policy and practice settings.